Stumbling through: Building and creating space for non-Indigenous decolonization from a non-Indigenous perspective - Cortney Baldwin (Adult Education Research Conference, 2019)
This paper utilizes theory and research to explore, create and reflect on building space for non-Indigenous people to begin to stumble through dialogue around decolonization and Reconciliation from a non-Indigenous perspective.
Keywords: Decolonization; Reconciliation; Adult Education; Transformative Pedagogy; Settler